Buddhist Values in Outdoor Learning: A Qualitative Study on Mindfulness and Behavioral Development in Early Childhood Education - Budarsana, I Gede; Astana, Astri Chintya; Susijati, Susijati (Abrahamic Religions: Jurnal Studi Agama-Agama, 2026)
Early childhood development faces significant challenges due to sedentary lifestyles and excessive screen time, affecting not only motor skills but also behavioral regulation and mindfulness. TK Nava Dhammasekha Dhamma Bakti Jaya has implemented Outdoor Learning since 2024; however, preliminary observations indicated that many children in group B still showed limitations in behavioral regulation and awareness during activities. This study aims to analyze the integration of Buddhist values in Outdoor Learning and its impact on mindfulness and behavioral development in early childhood education. This research employed a qualitative approach with an instrumental case study design conducted over five months (July–November 2024). The participants included 13 children in group B, 3 teachers, and 1 principal. Data were collected through participatory observation, semi-structured interviews, and documentation. Data analysis was carried out using reflective thematic analysis, with source and technique triangulation to ensure validity. The findings reveal that: (1) The integration of Buddhist values was implemented through three main mechanisms: breathing awareness before activities (sati), emphasis on effort rather than outcomes (viriya), and calm acceptance of failure (upekkhā); (2) Improvements in mindfulness and adaptive behavior were observed in 10 out of 13 children (76.9%), particularly in emotional regulation, attention focus, and calmness during activities; (3) Supporting factors included the availability of natural environments as learning affordances and strong teacher commitment, while inhibiting factors involved extreme weather conditions and parental safety concerns. In conclusion, integrating Buddhist values into Outdoor Learning effectively enhances mindfulness and adaptive behavior in early childhood through embodied awareness practices and the cultivation of perseverance. This model is particularly relevant for faith-based early childhood education, especially in rural contexts with limited resources